2016
DOI: 10.1097/nmd.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Exercise on Affect and Arousal in Inpatient Mental Health Consumers

Abstract: Acute exercise performed at a self-selected intensity improves affect and may improve long-term adherence. Similarly, in people with severe depression, acute aerobic exercise performed at self-selected intensity improves affect and arousal. However, the relationship between changes in affect and arousal and perceived exercise intensity in people with mental illness has not been evaluated. Affect and arousal were assessed immediately prior to, and immediately following, a group exercise program performed at a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
4
9
0
Order By: Relevance
“…Our findings resemble a previous investigation examining the effects of acute PE on core affects in adults with severe mental illness (depressive disorder, bipolar disorder and anxiety disorder) using the FS and the FAS (Stanton et al, 2016). Authors reported a significant increase of valence only among participants with bipolar disorder or depressive disorder but not anxiety disorder.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings resemble a previous investigation examining the effects of acute PE on core affects in adults with severe mental illness (depressive disorder, bipolar disorder and anxiety disorder) using the FS and the FAS (Stanton et al, 2016). Authors reported a significant increase of valence only among participants with bipolar disorder or depressive disorder but not anxiety disorder.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results but with higher effect sizes have been demonstrated in adults with generalized anxiety disorder (d = 1.01;Herring et al, 2019), major depressive disorder (d = 1.25;Meyer et al, 2016b) and obsessive-compulsive disorder (d = 0.76; Abrantes et al, 2009). Another study (Stanton et al, 2016) also measured the effect of a 20-minute session on core affects (valence and arousal) in individuals with anxiety, bipolar, and depressive disorders and reported an increase in arousal for individuals with depressive and bipolar disorders, and an increase in valence (more positive affects) in all the participants.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…18 Moreover, evaluation of the impacts of individualised interventions show condition-specific association with sleep 19 and acute changes in mood. 20 These findings highlight the importance of adapting PA interventions to the needs of the individual consumer.…”
Section: Exercise In the Inpatient Settingmentioning
confidence: 98%
“…For this reason, alternative treatment programmes that focus on the prevention of medical comorbidities in BD have to be implemented. Interventions that foster regular exercise and self-assessment of physical activities have to be developed for clinical practice [17,18].…”
Section: Introductionmentioning
confidence: 99%